Comparative Effectiveness of Reality Therapy and Emotion-Focused Therapy on Love Trauma Syndrome, Self-Worth, and Relationship Beliefs in Divorced Women in Tehran - Souri, Fatemeh; Jahangiri, Mohammad Mehdi; Pirani, Zabih (Applied Family Therapy Journal (AFTJ), 2025)
Objective: The present study aimed to compare the effectiveness of reality therapy and emotion-focused therapy (EFT) on love trauma syndrome, self-worth, and relationship beliefs in divorced women residing in Tehran. Methods and Materials: This research is applied in terms of purpose and quasi-experimental in terms of data collection, using a pretest-posttest-follow-up design with a control group. The statistical population included all divorced women residing in District 2 of Tehran in 2023, from whom 45 participants were selected through convenience sampling. The participants were randomly assigned, with age-matching, into two intervention groups and one control group. Participants completed the Relationship Beliefs Questionnaire, Ross’s Love Trauma Syndrome Questionnaire, and the Self-Worth Questionnaire at pretest, posttest, and follow-up phases. The first intervention group received 8 sessions of reality therapy, while the second group received 10 sessions of emotion-focused therapy. Data were analyzed using repeated measures analysis of variance (ANOVA) with SPSS version 22. Findings: Both reality therapy and emotion-focused therapy were effective in enhancing self-worth, improving relationship beliefs, and reducing love trauma syndrome symptoms among divorced women in Tehran. Moreover, the effectiveness of both treatments persisted over time. No significant difference was found between the effectiveness of reality therapy and emotion-focused therapy on the studied variables. Conclusion: Based on the results, it can be concluded that both reality therapy and emotion-focused therapy are effective interventions for improving love trauma syndrome symptoms, enhancing self-worth, and modifying relationship beliefs in divorced women in Tehran